Peningkatan Kompetensi CAD Bagi Siswa SMK Melalui Pelatihan Static Simulation Menggunakan Solid Works - Widya Sinta Mustika; Romiyadi Romiyadi; Yudi Dwianda; Adi Febrianton; Irwan, Purnama; Indah Purnama Putri (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Vocational education in the senior level, namlely Vocational High School (SMK), is designed to prepare graduates with high skills who are ready to compete in the work zone, both with competence and through entrepreneurship in order to face the demographic bonus. SMK Negeri 1 Bangkinang as a partner of the Politeknik Kampar has a major in the Mechanical Engineering. Generally, the major of Mechanical Engineering will be prepared in with competencies of Computer Aided Design (CAD). However, there are limitations to apply Solid Works software, which is currently in great demand in the industry. Therefore, the The major of Maintenance and Repair Engineering Politeknik Kampar participates in improving the competency of students at SMK Negeri 1 Bangkinang Kota through CAD Static Simulation Training activities using Solidworks Software. The training activity material contains an introduction to Solidworks, static simulation theory, namely stress, strain and deformation. At the end of the training activity session, an increase in partner competency was obtained regarding the use of Solid Works software in image creation and static simulation. Evaluation of activities through partner satisfaction questionnaires also found that partners were 100% satisfied with the PkM activities carried out.